Evaluation of single and combination chemotherapy agents in patients with metastatic breast cancer - Martanty Aditya; Godeliva Adriani Hendra; Suhul Raos Kumawula Ing Gustyas (Universitas Islam Indonesia, 2022)
Background: There are several ways to treat breast cancer, one of which is administering chemotherapy agents. Chemotherapy agents have activity in inhibiting the cell cycle. That will affect the effectiveness of therapy and the side effects of chemotherapy agents. Objective: This study aimed to evaluate single and combination chemotherapy agent therapeutic efficacy and side effects Method: The design of this study used an observational cohort study with retrospective data collection from January to December 2019. Patients obtained from medical records were diagnosed with metastatic stage of breast cancer at Panti Nirmala Hospital, Malang. The effectiveness of the chemotherapy agent was seen from the carcinoembryonic antigen (CEA) and cancer antigen 15-3 (CA15-3), which were carried out in the first and third cycles, then analyzed using the Wilcoxon and U-Mann Whitney tests. Side effects of chemotherapy agents were analyzed descriptively. Results: Analysis of the Wilcoxon test showed differences between the two groups of chemotherapeutic agents in CEA and CA15-3 (p<0.05). U-Mann Whitney test analysis showed no difference after administration of the two groups of chemotherapy agents at CEA (p>0.05). However, there was a difference in CA15-3 (p<0.05). Both chemotherapy agents showed most common side effects such as pain, nausea, vomiting, and alopecia. Conclusion: Patients who received a combination of chemotherapy agents had lower CA15-3 levels than single chemotherapy agents.